Antifungal Activity of Lactic Acid Bacteria Combinations in Dairy Mimicking Models and Their Potential as Bioprotective Cultures in Pilot Scale Applications - Leyva Salas, Marcia; Thierry, Anne; Lemaître, Mathilde; Garric, Gilles; Harel-Oger, Marielle; Chatel, Manon; Lê, Sébastien; Mounier, Jérôme; Valence, Florence; Coton, Emmanuel (Frontiers in Microbiology, 2018)
Consumer's demand for naturally preserved food products is growing and the use of bioprotective cultures is an alternative to chemical preservatives or a complementary tool to hurdle technologies to avoid or delay fungal spoilage of dairy products. To develop antifungal cultures for the dairy product biopreservation, experiments were conducted both in vitro and in situ. Firstly, the antifungal activity of 32 strains of lactic acid bacteria and propionibacteria was screened alone, and then on combinations based on 5 selected lactobacilli strains. This screening was performed in yogurt and cheese models against four major spoilage fungi previously isolated from contaminated dairy products (Penicillium commune, Mucor racemosus, Galactomyces geotrichum and Yarrowia lipolytica). Selected combinations were then tested as adjunct cultures in sour cream and semi-hard cheeses produced at a pilot scale to evaluate their antifungal activity during challenge tests against selected fungal targets (P. commune, M. racemosus and Rhodotorula mucilaginosa) and shelf life tests; and their impact on product organoleptic properties. The screening step allowed selecting two binary combinations, A1 and A3 composed of L. plantarum L244 and either L. harbinensis L172 or L. rhamnosus CIRM-BIA1113, respectively. In situ assays showed that the A1 combination delayed the growth of P. commune, M. racemosus and R. mucilaginosa for 2 to 24 days on sour cream depending of the antifungal culture inoculum, without effect on organoleptic properties at low inoculum (106 colony-forming units (CFU)/mL). Moreover, the A1 and A3 combinations also delayed the growth of P. commune in semi-hard cheese for 1 to 6 days and 1 day, respectively. Antifungal cultures neither impacted the growth of starter cultures in both sour cream and cheese nor their pH, a stronger post acidification was observed in sour cream supplemented with these combinations at the highest concentrations (2.107 CFU/mL). The combination of both in vitro and in situ screening assays allowed developing 2 antifungal combinations exhibiting significant antifungal activity and providing future prospects for use as bioprotective cultures in dairy products.